An NMR crystallography investigation of furosemide - Zilka, Miri (Magn Reson Chem, 2018)
This paper presents an NMR crystallography study of three polymorphs of furosemide. Experimental magic‐angle spinning (MAS) solid‐state NMR spectra are reported for form I of furosemide, and these are assigned using density‐functional theory (DFT)‐based gauge‐including projector augmented wave (GIPAW) calculations. Focusing on the three known polymorphs, we examine the changes to the NMR parameters due to crystal packing effects. We use a recently developed formalism to visualise which regions are responsible for the chemical shielding of particular sites and hence understand the variation in NMR parameters between the three polymorphs.